Timeless Treasures: The Journey of Rumah Warisan Uwan Robah (Ruwur) - Ummi Salwa Ahmad Bustamam; Nuruliza Roslan; Khairunneezam Mohd Noor; Izawati Wook; Suria Hani A. Rahman; Norsimaa Mustaffa (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025